LENGTH-WEIGHT RELATIONSHIP IN CATFISH TACHYSURUS TENUISPINIS (DAY) - Dan, S S; Mojumder, P (Indian Journal of Fisheries, 2011)
The kngth-weight relationship in the cat-fish, Tachyxitrus tenuispinis obtainedfrom two zones, the north (off False Point) and the south (off Visakhapatnam),was worked out. The deviations in regression co-efficients in respect of sexes aswell as zones were not significant. Hence a formula common to both sexes andregions was justified.